REKONSTRUKSI DEMOKRASI INDONESIA: INTEGRASI POLIARKI ROBERT A.DAHL DAN NILAI-NILAI ISLAM - Amir Hamzah (Wasīlah: Journal Of Sharia Sciences, 2026)
This study aims to discuss the problems of democracy in Indonesia and then use Robert A. Dahl's thoughts and Islamic values in reconstructing Indonesian democracy. This study uses a philosophical-critical literature review approach to data collected through journals, books, and websites related to the discussion. The results of this study indicate that the Indonesian democracy index has decreased in recent years, Robert A. Dahl suggests the concept of polyarchy which includes ways to improve the democracy index as well as Islamic values. The conclusion in this study is that the democracy index can be improved by applying Robert A. Dahl's ideas and Islamic values, including Syuro, Al-'Adalah, and Al Musawah.